Agric Based Battery - Ojugbani, Onyeka (My University, 2022)
When electricity passes through the system , the electron in the system becomes unstable. sodium ion is highly electronegative, the electron in sodium will pass through aluminum foil but gets trapped in the silicon and elephant grass electrolyte. Grass absorbs photon light from the sun in the process of photosynthesis but in this way the grass will store the electrons from electricity as photoelectric and also silicon is a good conductor for electricity, therefore electrons can feel comfortablein that region.Similarly the zinc will tend to sacrifice its electron because it is a highly active metal. but it will also be trapped in the electrolyte. Also fiber grass will block the electron from going out of the system till when it is needed. After it is successful charged, you can connect your phone and the electron stored in the electrolyte will charge them .
Keywords: Electricity; Agriculture